Kuntanshi yamikalile (The Future): speculative nonconformity in the works of Zambian visual artists - Mulenga, Andrew Mukuka (Rhodes University, Faculty of Humanities, Department of Fine Art, 2021)
In recent years, select African visual artists practising on the continent as well as in its diaspora have increasingly been attracted to themes that explore, portray or grapple with Africa's future. Along with this increasing popularity of the 'future' or indeed 'African futuristic' themes by visual artists, such themes have also attracted academic consideration among various scholars, resulting primarily in topics described as 'African Futurism' or Afrofuturism. These are topics that may be used to disrupt what some scholars "“ across disciplines and in various contexts "“ have highlighted as the persistent presumptive notions that portray Africa as a hinterland (Hassan 1999; Sefa Dei, Hall and Goldin Rosenberg 2000; Simbao 2007; Soyinka-Airewele and Edozie 2010; Moyo 2013; Keita, L. 2014; Green 2014; Serpell 2016). This study makes an effort to critique certain aspects of 'African Art History' with regard to the representation of Africa, and raises the following question: How can an analysis of artistic portrayals of 'the future' portrayed in the works of select contemporary Zambian artists be used to critique the positioning of Africa as 'backward', an occurrence at the intersection of a dualistic framing of tradition versus modern. Furthermore, how can this be used to break down this dichotomy in order to challenge lingering perceptions of African belatedness? The study analyses ways in which this belatedness is challenged by the juxtaposition of traditional, contemporary and futuristic elements by discussing a series of topics and debates associated to African cultures and technology that may be deemed disconnected from the contemporary lived experiences of Africans based on the continent. The study acknowledges that there is no singular 'African Art History' that one can talk of and there have been various shifts in how it has been perceived. I argue that while currently the African art history that is written in the West does not simplistically position Africa as backward as it may have done in the past, there appear to be moments of a hangover of this perception (Lamp 1999:4). What started out as a largely Western scholarly discourse of African art history occurred in about the 1950s and the journal African Arts started in the 1960s. Even before contemporary African art became a big thing in the 1990s for the largely US- and Europe-based discourses there were many discussions in the US about how the 'old' art history tended to freeze time and that this was not appropriate (Drewal 1991 et al). In order to advance the discourse on contemporary African visual arts I present critical analyses of the select works of Zambian artists to develop interpretations of the broader uses of the aforementioned themes. The evidence that supports the core argument of this research is embedded in the images discussed throughout this dissertation. The artists featured in the study span several decades including artists who were active from the 1960s to the 1980s, such as Henry Tayali and Akwila Simpasa, as well as artists who have been practising since the 1980s, such as Chishimba Chansa and William Miko and those that are more current and have been producing work from the early 1990s and 2000s, such as Zenzele Chulu, Milumbe Haimbe, Stary Mwaba, Isaac Kalambata and Roy Jethro Phiri.
Keywords: Future in art; Africa -- In art; Art, Zambian; Art, African; Artists -- Zambia; Nyandoro, Gareth